Exploring the Relationship between Safe Learning Environments and Literacy Skills in Majority Muslim Southeast Asian Nations: Insights from PISA 2022 - Haridza, Risa (Muslim Education Review, 2024)
This research investigates the association of safe learning environments with literacy scores in three Southeast Asian countries with Muslim-majority populations: Brunei Darussalam, Indonesia and Malaysia. The study will use data from PISA 2022 to identify factors that promote inclusive learning environments and are related to students’ literacy. The research is grounded in theoretical frameworks, such as Social Cognitive Theory, Ecological Systems Theory, and Cultural-Historical Activity Theory, to discern factors associated with students’ literacy and to develop strategies for creating inclusive learning environments. The data will be analyzed using Welch’s ANOVA, Post Hoc Comparison, and regression analysis. The results revealed that bullying, feeling unsafe, and school safety risks are negatively associated with students’ literacy scores and highlight the importance of creating inclusive learning environments. The study’s potential impact on future research and interventions is significant, making it a crucial foundation for further investigation.